Wave Computing in the Cloud - Yang, Mao; Guo, Zhenyu; Lin, Wei; Su, Bing; Zhou, Lidong; He, Saven (HotOS, 2009)
We introduce the new Wave model for exposing the temporal relationship among the queries in data-intensive distributed computing. The model deﬁnes the notion of query series to capture the recurrent nature of batched computation on periodically updated input streams. This seemingly simple concept captures a signiﬁcant portion of the queries we observed in a production system. The recurring nature of the computation on the same steam opens up surprisingly signiﬁcant opportunities for achieving better performance and higher resource utilization.